Can we use methylation markers as diagnostic and prognostic indicators for bladder cancer? - Yong-June Kim; Wun-Jae Kim (Investigative and Clinical Urology, 2016)
Urothelial carcinomas of the urinary bladder have diverse biological and functional characteristics, and numerous factors are likely to be involved in recurrence, progression, and patient survival. While several molecular markers used to evaluate the development and prognosis of bladder cancer have been studied, they are of limited value; therefore, new molecular parameters useful for predicting the prognosis of bladder cancer patients (particularly patients at high risk of progression and recurrence) are required. Recent progress in the understanding of epigenetic modification and gene silencing has provided new opportunities for the detection, treatment, and prevention of cancer. Methylation is an important molecular mechanism in bladder cancer and may have utility as a prognostic and/or diagnostic marker. This review discusses the epigenetic issues involved in the detection and prediction of bladder cancer.